Development and Evaluation of Loratadine and Montelukast Sol Gel - Abu Ans Waseer; Muhammad Umar Safda; Muhammad Bilal Rana; Momin Shah; Ayan Amir; Muhammad Irfan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The traditional oral treatments of allergic rhinitis and smog-related respiratory disease are impaired by limited bioavailability, slow action, and systemic adverse effects which can be explained by the hepatic first-pass metabolism. Objectives: The current research was conducted to create and to test a thermo-responsive, mucoadhesive in-situ nasal gel co-loaded with Montelukast and Loratadine in order to increase bioavailability, fast onset, and prolonged symptom relief. Methods: Poloxamer 407 and HPMC were used in the preparation of the formulation via cold-start procedure, yielding a nasal temperature sol-to-gel transition. Extensive physicochemical characterisation was conducted and included pH, viscosity, gelation time, spreadability, mucoadhesion and in-vitro release. Results: The optimised formulation had a suitable gelation at 3234o C, a strong mucoadhesive force (approximately 6900 dyn cm -2), and was able to release the drug at a higher percentage (more than 90 per cent) over 12 hours. FTIR spectroscopy was used to identify compatibility of drug and excipient whereas stability tests proved the presence of good physicochemical and microbial integrity at accelerated conditions. Conclusion: The thermoresponsive nasal gel mitigated the limitations of oral therapy by offering better nasal retention, release control and higher patient compliance, which is an exciting and non-invasive therapeutic option to respiratory allergies and pollution-related ailment(s). Limitations: Further in vivo and clinical validation is required to confirm pharmacokinetic performance and safety.